’The Wheel is Crooked’: Hannah Arendt on action, success and public happiness - Cain, Alex (HannahArendt.net, 2024)
In “Action and the ‘Pursuit of Happiness,’” Hannah Arendt tells the story of “an inveterate gambler” who arrives late in a town and goes straight to the gambling place, where he discovers that the wheel he wishes to gamble on is crooked. He gambles anyway, because there is no other wheel in town. The story, she suggests, “tells us that there exists such intense happiness in acting that the actor, like the gambler, will accept that all the odds are stacked against him.” In this article I use this story as a motif to investigate references to success in Arendt’s work. I argue that Arendt sought to preclude action and happiness from utilitarian notions of success, and that she ultimately presents the human impulse toward action as tragic. I also discuss the role of the historian or poet in this tragedy, concluding that what remains unclear in Arendt’s work is how the public happiness of the actor and the pleasure of the historian and poet are related.